2016
DOI: 10.1111/rda.12667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temporary Meiotic Attenuation of Oocytes with Butyrolactone I and Roscovitine in Resistance to Bovine Embryos on Vitrification

Abstract: This study aimed to produce in vitro bovine embryos by the addition of two drugs, which is responsible for oocyte meiosis inhibition: roscovitine (ROS) and butyrolactone I (BL-I). Oocytes were recovered from slaughtered cows and matured in a commercial medium and maintained in a 5% CO2 atmosphere. Oocytes were maintained for 6 h in an in vitro maturation (IVM) medium containing ROS (12.5 μm), BL-I (50 μm) and association of drugs (ROS 6.25 μm and BL-I 25 μm). Oocytes were cultured for 18 h in an agent-free med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…). A recent study has also concluded thatcombination of inhibitors is better not only in maintaining the oocytes at GV stage but also in improving their future development competence [Maziero et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…). A recent study has also concluded thatcombination of inhibitors is better not only in maintaining the oocytes at GV stage but also in improving their future development competence [Maziero et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In each experimental group, oocytes were randomly collected at 6, 12 or 24 h of pre-IVM and 12, 18 or 24 h of IVM (n = 3058). Collection was performed as previously described by Maziero et al (2016).…”
Section: Evaluation Of Oocyte Nuclear Stagementioning
confidence: 99%
“…Spontaneous oocyte maturation can be avoided by using specific cyclin-dependent kinase (CDK) inhibitors such as butyrolactone I (BL-I) and roscovitine (ROS), which inhibit activity of oocyte maturation promoting factor (MPF) (Adona et al, 2008;Quetglas et al, 2011;Maziero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para a fertilização in vitro (FIV) utilizou-se sêmen de um único touro da raça Holandês (diferentes partidas de congelação), descongelado por 30 segundos em banho-maria a 36 C°. Para a separação dos espermatozoides viáveis, realizou-se centrifugação em gradiente de Percoll (Maziero et al, 2016) e os oócitos foram incubados por 20 horas, em gotas de 10 μL com meio FIV (comercial da empresa), contendo até 30 oócitos/gota.…”
Section: Produção In Vitro De Embriõesunclassified